LUNG ULTRASOUND IN THE DIAGNOSIS OF MECONIUM ASPIRATION SYNDROME IN NEONATES: A SYSTEMATIC REVIEW - Mazurek, Katarzyna; Wojciechowicz, Marek; Brzęcka, Marta; Rogiński, Stanisław; Chojnowski, Łukasz; Dominiczak, Anna; Rogiński, Krzysztof; Szlęzak, Ksawery; Kryca, Karolina; Rogińska, Karolina (International Journal of Innovative Technologies in Social Science, 2026)
The aim of the study: Meconium aspiration syndrome (MAS) remains an important cause of neonatal respiratory distress and is traditionally diagnosed using clinical criteria supported by chest X-ray. Lung ultrasound (LUS) is a radiation-free, bedside imaging modality increasingly used in neonatal lung diseases. The objective of this systematic review is to evaluate the diagnostic role of LUS in neonates with MAS. Materials and methods: A systematic literature search was conducted in PubMed and Google Scholar in accordance with the PRISMA 2020 guidelines. Original studies involving neonates with MAS and reporting MAS-specific LUS data were included. Studies were excluded if they were non-English, animal studies, lacked original data, involved non-MAS populations or focused on therapy guidance rather than diagnosis. Results: Five studies met the inclusion criteria. Across the included studies, LUS demonstrated high diagnostic performance for MAS, with reported sensitivity ranging from 90% to 100% and specificity 99.3% to 100%. Characteristic LUS findings included lung consolidations with air bronchogram, pleural line abnormalities, disappearance of A-lines and alveolar-interstitial syndrome. Conclusions: LUS appears to be a reliable diagnostic tool for MAS and offers important advantages including absence of ionizing radiation and bedside applicability. It may be considered a first-line imaging modality in infants with suspected MAS, with chest X-ray reserved for cases of diagnostic uncertainty. Further studies are needed to confirm these findings.